Kinerja Analisis Kinerja Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat dengan Metode Balance Score Card - Maulana, Afif; Saimi; Khalik, Lalu Abdul (Journal of Health Science and Prevention, 2025)
Performance measurement is one of the important factors in a business organization, including BLUD, as mandated in Permendagri Number 79 of 2018. The purpose of this study was to analyze the performance of the NTB Provincial Hospital using the Balance ScoreCard method. The research method used a descriptive qualitative approach. Data collection was carried out through direct observation, in-depth interviews with seven informants, and documentation (document analysis). The results showed that the performance of the NTB Provincial Hospital in the customer perspective was rated quite good, as evidenced by the level of customer satisfaction with tangibles and assurance in the satisfied category, while in the aspects of reliability, empathy, and responsiveness, it was in the quite satisfied category. In the financial perspective, the solvency ratio and collection period are better than the ideal standard, while the liquidity ratio, total assets turnover, and cost recovery rate are less than the ideal standard. In the internal business process perspective, the NTB Provincial Hospital showed fairly good performance in most indicators; however, the high GDR and NDR rates indicate challenges in terms of the quality of critical patient care and mortality management. From the learning and growth perspective, the results are quite good with continuous employee competency development. NTB Provincial Hospital can start the process and efforts to improve performance by increasing the ability and motivation of HR work and innovation in the utiliz s of service information systems (learning and growth perspective), in order to improve the effectiveness and efficiency of business processes as an effort to improve the quality and quality of services provided to patients (internal business process perspective), thus customers will feel comfortable, trust, and be satisfied with the services provided by the hospital (increased customer perspective), until finally the hospital's income will also increase (financial perspective).